2018
DOI: 10.1038/s41419-017-0069-5
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the role of PIKK family members and NF-кB in DNAdamage-induced senescence and senescence-associated secretory phenotype of colon cancer cells

Abstract: Senescence of cancer cells is an important outcome of treatment of many cancer types. Cell senescence is a permanent cell cycle arrest induced by stress conditions, including DNA damage. DNA damage activates DNA damage response (DDR), which involves members of the phosphatidylinositol 3-kinase-related kinase (PIKK) superfamily: protein kinases ATM, ATR, and DNA-PKcs. The so-far collected data indicate that ATM, with its downstream targets CHK2, p53, and p21, is the key protein involved in DDR-dependent senesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 61 publications
3
25
0
Order By: Relevance
“…In recent years, clinical evidence has shown that postoperative tumors are insensitive to radiotherapies and chemotherapies, which is associated with increased NF-κΒ activity [19,32]. Anticancer radiotherapies generally eliminate tumor cells by damaging DNA, inducing apoptosis, and blocking tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, clinical evidence has shown that postoperative tumors are insensitive to radiotherapies and chemotherapies, which is associated with increased NF-κΒ activity [19,32]. Anticancer radiotherapies generally eliminate tumor cells by damaging DNA, inducing apoptosis, and blocking tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κΒ is also known to prevent apoptosis through its involvement in cell cycle arrest and DNA repair, and plays an important role in tumor proliferation and apoptosis [16,17]. In many types of tumors, structural activation of NF-κΒ is involved in tumor resistance to chemotherapy and radiotherapy [18,19]. NF-κΒ and NF-κΒ-regulated gene products, including Bcl-xl, cyclin D1, matrix metalloproteinase-9 (MMP-9), vascular endothelial growth factor (VEGF), and cyclooxygenase-2 (COX-2), are involved in tumor cell resistance to radiotherapy [20,21].…”
mentioning
confidence: 99%
“…The same results were found when HCT116 or MCF7 cell lines were treated with 100 nM of Dox [2,27,28]. HCT116 exposed to 50 nM [29][30][31], 75 nM [32], 100 nM [2,31,[33][34][35][36], and 200 nM [37] for 1-4 days exhibited the features of senescence. Higher doses of Dox induced senescence in HCT116 by doses of 1 µM for 2 h [38] and 500 nM for 4 h [39].…”
Section: Discussionsupporting
confidence: 76%
“…It seems however, that DNA damage can evoke cell senescence even when DDR is not fully activated due to mutations in genes encoding the effector proteins that may occur in cancer and non-cancer cells. In fact, we documented this for HCT116 p53-deficient cancer cells [Mosieniak et al, 2012;Strzeszewska et al, 2018] and for an immortal line of lymphocytes derived from a patient with Nijmegen Breakage Syndrome (NBS) caused by mutation in the nibrin gene [Alster et al, 2014]. In normal VSMCs undergoing curcumin-induced senescence we showed activation of ATM but, unexpectedly, ATM silencing had no effect on cell senescence [Grabowska et al, 2015].…”
Section: Dna Damage Response and Cell Senescencementioning
confidence: 72%
“…This implies that even if activated, ATM is not the crucial for transducing the signal for cell senescing. Indeed, our recent results led us to the conclusion that ATR, but not ATM kinase, is crucial for the onset of senescence in HCT 116 cells [Strzeszewska et al, 2018]. However, ATR does not play important role in curcumin-induced senescence of VSMCs (submitted), which indicates cell senescence diversity.…”
Section: Dna Damage Response and Cell Senescencementioning
confidence: 99%